IDENTIFYING FACTORS CONTRIBUTING TO STUDENTS’ OBSTACLES IN UNDERSTANDING READING DESCRIPTIVE TEXT - Rahmayanti Rahmayanti; Rini Susiani; Putri Dini Meutia; Ferlya Elyza; Ema Dauyah (Jurnal Dedikasi Pendidikan, 2023)
This study aimed to analyze the students’ obstacles in understanding reading descriptive text since there were many problems that the students encounter in understanding reading text. The method used in this study was a descriptive quantitative through test and questionnaire as data collection instruments.  The questionnaire consisted of items to gain the students’ responses towards 3 categories of students’ difficulties factors in reading, namely: learners’ background, teaching technique, and learners’ environment. Seventeen first-grade students in a senior high school in Aceh Besar were involved as participants. The result of students’ reading comprehension test showed that 86,6 % of students were not able to identify references in the text, and 70,6 % of students found difficulty in making inferences in the text. The result of the questionnaire further showed that 71,9% of students agreed toward a lack of interest in reading descriptive text, and 73,5% of students agreed that students’ background knowledge affects their reading comprehension, especially in reading descriptive text. It can be concluded that most of the students found difficulty in identifying and making references in the text, whereas the questionnaire result showed that most of the students lack of background knowledge and interest in reading descriptive text